Judicialização da saúde pública no Piauí, Nordeste do Brasil: dimensões e desafios a partir do judiciário - Andrade, Nayla Rochele Nogueira de (2022)
Judicialization of the right to health consists in the filing of actions requesting goods and/or services in health, using the Judiciary as an instrument of access to health. Part of the doctrine understands that the instrument is beneficial, it is part of the strengthening of democracy and citizen's conscience in the search for the right guaranteed by the Constitution of 1988. Another group understands to cause problems, characterizes budgetary impact and judicial activism in the creation of public policies not endorsed by the executive. Regardless of the setbacks, lawsuits requesting these procedures are growing. Its real dimension and challenges are unknown, as well as whether there is a judicialization of the right to health for neglected tropical diseases. Thus, a guiding question was adopted: what is the dimension and challenges of the judicialization of the right to health in the State of Piauí from 2000 to 2020? A descriptive crosssectional study, supported by document analysis and secondary indicators was performed. The study took place in phases, the first was a survey of the judicialization of the right to health processes with a view to its dimension, verifying temporal and spatial patterns. The second consisted of describing sociodemographic and clinical profile of subjects involved in the demands, as well as the objects demanded, operationalization of judicial processes, and databases of the Courts of Justice of Brazil to access health processes. As a result of the second phase, it verified the participation of neglected tropical diseases in this phenomenon in Piauí. A total of 6,658 cases classified as health demands in the face of the Direct Public Administration were identified. After analysis of eligibility, 1,384 (20.8%) processes were analyzed in the databases (PJE1G and PJE2G). Most in the region of Teresina (614; 44.4%), female (761; 55%), age group 40 to 59 years (372; 26.9%), farmers (123; 8.89%), assistance public legal system (1,063; 76.8%), Applications upheld (594; 42.9%), Favorable opinion from the Judicial Support Center (629; 45.4%). Lawsuits requesting medication (571;41.3%), made available by the Unified Health System (847; 61.2%), the most requested medication was enoxaparin (49;5.32%). Identified (5; 0.4%) demands for NTDs, four related to leprosy, 2 requesting medication, one referred to thalidomide for leprosy reaction treatment, a medical consultation and a complementary exam, all granted. There was a demand for visceral leishmaniasis requesting transport for treatment, demand granted. The judicialization of health is expressive and growing in the State of Piauí. There are specificities of the plaintiffs and the defendant objects, it requires a more systematic evaluation of the judiciary's databases. The judicial route has been consolidated as a form of access to medicines incorporated into the SUS, due to shortages, lack of programming and governance in public health policies. The low demand related to NTDs can translate into limited access not only to healthcare, but also to the judiciary.